Controle ativo de vibrações laterais em rotores flexíveis usando atuadores magnéticos - Abreu, Gustavo Luiz Chagas Manhães de (1998)
This work proposes a methodology of active control for lateral displacements in flexible rotors caused by disturbance forces. The controller designed was based on the classic control theory and the action of magnetic bearing that presents linear characteristics within the nominal operating conditions. This work presents the theoretical elements for the controller, the mathematical model of the rotor which is discretized by finite elements and the mathematical model of the force generated by a magnetic bearing. The efficiency and the potentiality of the theoretical procedure are shown through numerical simulations. The flexible rotor, the magnetic bearing, the sensors and the control electronic are shown and the theoretical procedures are investigated. An experimental apparatus representing a rotor/bearings system is used to identify the static and dynamic parameters. A set of experimental tests are made to evaluate the proposed controller action under several operating conditions of the rotor. This work is concluded presenting the potentialities of the design methodology proposed and future developments to be implemented.